Are metals in exhaled breath condensate and urine associated with oxidative/nitrosative stress and metabolism-related biomarkers? Results from 303 randomly selected Parisian subway workers - Sauvain, J.J.; Wild, P.; Charreau, T.; Jouannique, V.; Sakthithasan, K.; Debatisse, A.; Suárez, G.; Hopf, N.B.; Guseva Canu, I. (Environment international, 2025)
[Display omitted] •Metals associated with anions in exhaled breath condensate (EBC)•Urinary metals associated with oxidative stress biomarkers in subway workers.•Job associated with urinary Ba and Ti and small chain fatty acids in EBC.•Smoking associated with effect biomarkers, not with exposure biomarkers. Subway particles can cause oxidative stress, with metals being a key factor. Only few epidemiological studies have examined the role of metal mixtures in this effect for subway workers. This cross-sectional study examined the relationship between metal concentrations in exhaled breath condensate (EBC) and urine, and biomarkers of oxidative/nitrosative stress and metabolism in subway workers. The study involved 303 randomly selected Parisian metro workers exposed to various levels of subway particles. Metals in EBC and urine were measured using ICP-MS, and biomarkers were analyzed through liquid chromatography-mass spectrometry. Factor analysis as dimension reduction strategy and cluster analysis to account for metal mixtures and multiple multi-media effect biomarkers was used along with multivariable linear regression analysis on factor variables adjusted for potential confounders. Significant positive associations were observed between urinary metals and oxidative stress biomarkers, despite similar metal levels in workers and the general population. Metals in EBC were linked to nitrosative stress and other metabolites in EBC. Worker occupation correlated with small chain fatty acids in EBC and urinary levels of barium and titanium. Smoking was associated with effect biomarkers but not with exposure biomarkers. Elevated metal levels in EBC and urine are associated with altered bronchopulmonary metabolites and increased systemic oxidative stress. While Ba and Ti may originate from brake wear, other metals identified in EBC and urine are not clearly related with subway particles and may be from non-occupational sources. Smoking showed a stronger relationship with the workers’ oxidative stress status than occupation.